Critical Discourse Analysis: The Negative Representation of the French President in France's English Online News - Anggraeni, Yulia; Citraresmana, Elvi; Koeshandoyo , Eko Wahyu (Universitas Lancang Kuning, 2022)
There is a scarcity of Critical Discourse Analysis (CDA) studies on the representation of social actors in news media, thus this study addressed this research gap by analysing the way news represented the French President Emmanuel Macron, regarding his controversial support of Samuel Paty, a history teacher in France who was murdered because he showed a cartoon of Prophet Muhammad in his class. This research aims to see the representation of Emmanuel Macron from the perspective of the French media, The Connexion France, which published their news in English language online to reach world-wide audience. Four articles of the news were purposively selected for this CDA study, which were published from October 18 until November 1, 2020. The French President’s representation was analysed with the nomination and predication strategies. Results showed that the Connexion France uses four nomination strategies to refer Emmanuel Macron. The professional anthroponyms refer to Emmanual Macron as “the President”, proper names as “Emmanuel Macron” to be the centre of the discourse, synecdoche as “Emmanuel Macron”, and deixis as “he” to avoid repetition the subject of the text. Two predication strategies were also used, the explicit predicate of how the President “has promised” action against Islamists and presupposition from the way the news linked pictures of boycotted French supermarket products with the President. This research provides a take on fresh news with CDA and can beneficial for the students who learn English language by showing how the media uses language for political figures.